2015
DOI: 10.1542/peds.2014-1416
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting Breastfeeding Support and Exclusive Breastfeeding: A Randomized Controlled Trial

Abstract: OBJECTIVE: To evaluate the effectiveness of a coparenting intervention on exclusive breastfeeding among primiparous mothers and fathers.METHODS: A randomized controlled trial was conducted in a large teaching hospital in Toronto, Canada. Couples were randomized to receive either usual care (n = 107) or a coparenting breastfeeding support intervention (n = 107). Follow-up of exclusive breastfeeding and diverse secondary outcomes was conducted at 6 and 12 weeks postpartum.RESULTS: Significantly more mothers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 31 publications
3
109
1
5
Order By: Relevance
“…In addition, interventions that involve fathers, grandmothers, and/or other identified sources of social support may be more successful. 38 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, interventions that involve fathers, grandmothers, and/or other identified sources of social support may be more successful. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Four trials examined parenting efficacy, which refers to the beliefs parents hold about their ability to parent successfully. Three trials reported no effects on fathers’ parenting efficacy or competence (Fagan, ; Frank, Keown, & Sanders, ; Roskam, ) while one trial found an increase in paternal breast‐feeding self‐efficacy (Abbass‐Dick et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…One intervention also provided information about ways to reduce breastfeeding barriers to both parents via fathers for 5 weeks following birth (Tohotoa et al., ). However, only Abbass‐Dick, Stern, Nelson, Watson, and Dennis () directly addressed the relational aspects of support provision. In a randomized controlled trial of a coparenting breastfeeding support intervention with couples recruited on a postpartum unit, intervention parents were provided with a brief information session and a breastfeeding coparenting video, booklet, and website, and received two emails and a phone call in the first 3 weeks postpartum.…”
Section: Father Involvement Intervention In Vietnammentioning
confidence: 99%